MENGINTEGRASIKAN NILAI KEAGAAMAN MELALUI PENGABDIAN MASYARAKAT DI DESA MALAKONI, PULAU ENGGANO - Wardoyo , Sapto; Octaviani , Winda; Nurputri , Dygta; Mesha , Agita; Yosia , Yangke; Jaya , Purnama; Rohmadina, Rohmadina; Yuliarti , Nadia; Cahya , Indah Mutia; Sugiarto , Dendi; Nurhayati , Siti (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Community service is an activity carried out by universities as a form of implementation of the Tri Dharma of Higher Education, with the aim of helping the community in solving problems, in order to form a prosperous society, and as a learning process for living in society. The methods used are surveys, interviews and community approaches. So that the results of this community service show that with community service, it can help a little with the problems that exist in society by increasing the assets that have been owned by the community, namely spiritual assets which are the main capital for forming a civilized society with a framework of community and religious rules. The work programs that have been implemented have also succeeded in strengthening the ties of friendship between religious communities, and have been able to increase religious understanding and knowledge of the development of technology and information. The integration of these religious values ​​has been proven to be able to strengthen social cohesion and build better community character. The conclusion of this study is that community service based on religious values ​​can be an effective strategy in building a more harmonious and sustainable society.